Comparison of heat units methods and calendar date in predicting development stages of sunflower crop - Sangoi, Luis; Silva, Paulo Regis Ferreira da (Pesquisa Agropecuaria Brasileira, 2014)
The efficiency of three heat units methods and calendar date in predicting development stages of two sunflower cultivars, Contisol and Contisol 711, were evaluated. Heat units methods were more efficient than calendar date in predicting the stages of emergence to inflorescence head differentiation and emergence to beginning of anthesis. Differences were not observed among heat units methods.